Тhe role of defensins in the development of pathologic process: new approaches to diagnosis and treatment (literature review) - E. V. Dudnikova; A. S. Badyan (Медицинский вестник Юга России, 2015)
This literature review summarises and evaluates existing data about properties and biological activity of defensins, more particularly about their antibacterial, antiviral, antifungal, anticancer, anti-inflammatory activity, their role in the genesis of various diseases, as well as new perspectives for the use of presented cationic antimicrobial peptides in diagnosis and treatmentof different pathologies.